2021
DOI: 10.1111/ppc.12781
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID‐19, poor quality of sleep, irritability, and intention to quit school among nursing students: A cross‐sectional study

Abstract: Purpose This study aims to assess the fear of coronavirus disease 2019 (COVID‐19) and its influence on the students' fear of COVID‐19 and intention to leave nursing school. Design and Methods This study employed a cross‐sectional design using self‐report questionnaires distributed to 261 nursing students from the Philippines. Findings The first‐year nursing students are found to be the most fearful among the group. The students' fear of COVID‐19 is associated with their high irritability, poor sleep quality, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 51 publications
(51 reference statements)
5
61
1
4
Order By: Relevance
“…In regular periods, about 28% of Flemish nursing students occasionally considers leaving the nursing program ( Van Hoek et al, 2019 ). These findings seem to indicate that the CoViD-19 pandemic, although often perceived as challenge by students ( De Los Santos et al, 2021 ) does not coincide with a higher intent to leave the nursing education in the present sample. One could argue that might have to do with the fact that the societal and personal value of being a nurse was more clear during this pandemic.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In regular periods, about 28% of Flemish nursing students occasionally considers leaving the nursing program ( Van Hoek et al, 2019 ). These findings seem to indicate that the CoViD-19 pandemic, although often perceived as challenge by students ( De Los Santos et al, 2021 ) does not coincide with a higher intent to leave the nursing education in the present sample. One could argue that might have to do with the fact that the societal and personal value of being a nurse was more clear during this pandemic.…”
Section: Discussioncontrasting
confidence: 59%
“…This notably positive study commitment is encouraging to retain nursing students, and is also seen in a non-crisis related interview study by Clements et al (2016) , and a longitudinal study of ten Hoeve et al (2017) . Interview studies during the CoViD-19 pandemic specifically also reported high levels of commitment among final-year nursing students ( Gómez-Ibáñez et al, 2020 ).With 6%, the intention-to-leave was in line with the low levels reported in pandemic related studies ( De Los Santos et al, 2021 ; Nie et al, 2021 ), although relative low compared to regular periods. In regular periods, about 28% of Flemish nursing students occasionally considers leaving the nursing program ( Van Hoek et al, 2019 ).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…During the pandemic, students had to face several negative emotions such as feelings of loneliness, fear, and stress triggered by physical isolation during lockdowns, quarantines, or the measures implemented by governments (Wang et al, 2020;Awoke et al, 2021). A study at universities in the Philippines showed social and emotional support are important factors for reducing these negative feelings (De Los Santos et al, 2021).…”
Section: Dealing With Online Scientific Information About Covid-19mentioning
confidence: 99%